The Outer Membrane Vesicles of Aeromonas hydrophila ATCC® 7966TM: A Proteomic Analysis and Effect on Host Cells - Avila-Calderón, Eric Daniel; Otero-Olarra, Jorge Erick; Flores-Romo, Leopoldo; Peralta, Humberto; Aguilera-Arreola, Ma. Guadalupe; Morales-García, María Rosario; Calderón-Amador, Juana; Medina-Chávez, Olin; Donis-Maturano, Luis; Ruiz-Palma, María del Socorro; Contreras-Rodríguez, Araceli (Frontiers in Microbiology, 2018)
Gram-negative bacteria release outer membrane vesicles (OMVs) into the extracellular environment. OMVs have been studied extensively in bacterial pathogens, however information related with the composition of Aeromonas hydrophila OMVs is missing. In this study we analyzed the composition of purified OMVs from A. hydrophila ATCC® 7966™ by proteomics. Also we studied the effect of OMV on human peripheral blood mononuclear cells (PBMCs). Vesicles were grown in agar plates and then purified through ultracentrifugation steps. Purified vesicles showed an average diameter of 90-170 nm. Moreover, 211 unique proteins were found in OMVs from A. hydrophila; some of them are well-known as virulence factors such as: haemolysin Ahh1, RtxA toxin, extracellular lipase, HcpA protein, among others. OMVs from A. hydrophila ATCC® 7966™ induced lymphocyte activation and apoptosis in monocytes, as well as over-expression of pro-inflammatory cytokines. This work contributed to the knowledge of the composition of the vesicles of A. hydrophila ATCC® 7966™and their interaction with the host cell.